2019
DOI: 10.1353/hpu.2019.0052
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Health among Home Care Aides: Caring for Older Clients in a Medicaid-Funded Home Care Program

Abstract: Home care aides (HCAs) provide housekeeping and personal care services to help older clients remain in the community. However, little is known about the health of HCAs, who themselves constitute an underserved population. The goal of this study was to investigate how HCAs’ work and life contexts manifest themselves in HCAs’ health as perceived by HCAs. Six focus groups were conducted with HCAs (N=45). Analysis revealed how HCAs’ work-and life-related stress accumulated over time and affected HCAs’ health and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 35 publications
7
58
0
Order By: Relevance
“…The researchers used different qualitative research methods in their studies. The majority of studies (N = 9) used focus group interviews as the only method [26][27][28][29][30][31][32][33][34]. Seven studies used face-to-face interviews [35][36][37][38][39][40][41], while five studies used telephone interviews [42][43][44][45][46].…”
Section: Methodological Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…The researchers used different qualitative research methods in their studies. The majority of studies (N = 9) used focus group interviews as the only method [26][27][28][29][30][31][32][33][34]. Seven studies used face-to-face interviews [35][36][37][38][39][40][41], while five studies used telephone interviews [42][43][44][45][46].…”
Section: Methodological Approachesmentioning
confidence: 99%
“…One study reported that chronic pain and injuries in the lower back, shoulders, knees and neck resulted in surgery [36]. Strenuous work tasks included assisting clients with activities of daily living, performing housekeeping tasks or cleaning [26,32,35,36,42,47], transferring, assisting, repositioning and turning clients [28,32,35,36,42,47,49] and other heavy lifting [28,30,35,36,45,47,49]. Several informants experienced being in danger through physical violence from clients with mental health issues, dementia or Alzheimer's disease [30,32,33,35,36,40,[43][44][45]].…”
Section: Exposure To Physical Demandsmentioning
confidence: 99%
See 3 more Smart Citations